SOCIAL MOVEMENTS IN IRAQ AFTER 2003: CHARACTERISTICS, SOCIAL BASES AND SAMPLES - Ahmed Tahir Kadhim,; Salah Kadhim Jaber, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Sociologists who studied social movements (e.g., Tilly, 2005) regard social movements a prominent sign of the vitality of societies and their endeavour to accept and enact social change. This study is an attempt to explore the important social bases of social movements that appeared in Iraq after 2003. These movements invested in the fundamental changes that happened in Iraqi society after 2003, because they found a space of freedom to work in public and demand the goals that the participants shared and supported. What must be mentioned here is the dominance of an idea among Iraqi scholars and sociologists that the social movements are the protest movements which demand reforms. Other movements are only social deviations from the norms, traditions and basic cultural principles of the society which may cause ideological changes as the case with the general social perception of democracy. To achieve the purpose of this study, the researchers utilised social survey to collect data from a representative sample of the target community. The results show that there are several bases on which the social movements were established and developed. These bases include the deficiency of social construction institutions, the absence of social justice, the ambitions of marginalised groups and the multiple group identities that emerged in Iraq after 2003.